GLOBAL NARRATIVES IN LOCAL FRAMES: LINGUISTIC AND CULTURAL DYNAMICS OF MOTU PATLU IN CROSS-CULTURAL ANIMATION - Krishna, Kota Sai; Madhavi, P. Asha; Seshagiri, H (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study explores Motu Patlu, an Indian animated series, as a case study of cultural representation and global appeal in contemporary animation. Through a qualitative analysis of selected episodes, audience feedback, and comparative evaluation with globally recognised animated series such as Doraemon and Shaun the Sheep, the research examines how the show integrates Indian cultural markers with universal themes to engage diverse audiences. Anchored in theories of media globalisation, linguistic relativity, and audience reception, the study highlights Motu Patlu’s dual ability to celebrate Indian traditions while resonating with international viewers. Key findings reveal that Motu Patlu employs cultural elements like festivals, traditional foods, and regional dialects to reflect its Indian origins, while leveraging slapstick humour and universal values such as friendship and community to transcend linguistic and cultural boundaries. Audience sentiment analysis underscores a predominantly positive reception, with both Indian and non-Indian viewers appreciating the show’s humour and character dynamics. Comparative analysis situates Motu Patlu within the global animation landscape, showcasing its effective balance between cultural specificity and universal relatability. The study concludes that Motu Patlu exemplifies the potential of animated media as a tool for cultural exchange, offering insights into how local narratives can achieve global resonance while preserving their cultural identity.